Life cycle assessment of building construction materials: case study for a housing complex - Gonçalves de Lassio, João Gabriel; Naked Haddad, Assed (Revista de la Construcción. Journal of Construction, 2016)
In the present work, environmental impacts of building materials used in the construction of a housing project in the city of São Gonçalo, state of Rio de Janeiro, Brazil, have been assessed through Life Cycle Assessment (LCA) methodology in order not only to assist the decision-making of private and public nature, but also to promote life cycle thinking in the construction industry. Based on the guidelines set by ISO 14040 and ISO 14044, the LCA methodology has been applied with available databases and SimaPro program. The results show a considerable consumption of non-renewable energy, intensification of global warming and toxicity to human health. Moreover, this study exposes a necessity of action on the chain of production of steel, cement and ceramic materials mainly. Ceramic materials usage is also a factor the must be observed in detail due its elevated consumption.